Connecticut NAACP keeping education a top priority, including charter school concerns - Ortiz, Juliemar (TCA Regional News, 2016)
The board said it wanted charter schools to be subject to the same transparency and accountability standards as public schools, that public funds not be given to charter schools at the expense of the public school system, that charter schools stop expelling students that public schools have a duty to educate, and that charter schools stop "to perpetuate de facto segregation" of high performing children from children whose "aspirations may be high but whose talents are not yet as obvious.